Framing of Oil Spillage and Gas Flaring in Rivers State in Three Selected Nigerian Newspapers - Ata-Awaji Reuben; Nyerhovwo MUOBOGHARE; Bassey IKOT-OSIN; Soibi ORUWARI; Etimbuk OBOT; Emmanuel Omula; Theresa LINUS; Peace OJONTA; Simon SHEYIGARI (Ianna Journal of Interdisciplinary Studies)
Background: Oil spillage and gas flaring constitute some of the environmental pollutions confronting humanity, especially in oil producing countries and communities, like those in the Niger Delta region of Nigeria. This situation affects aquatic and human lives, with economic, social and health consequences. Amid these consequences, communication scholars are unanimous about the efficiency of framing of an issue such as oil spillage and gas flaring by the mass media on policy making and salvaging of situations.